Surfactant-associated bacteria in the near-surface layer of the ocean from in-situ DNA sampling and SAR imaging - Soloviev, A.; Howe, K.; Dean, C.; Tartar, A.; Shivji, M.; Haus, B.; Perrie, W.; Lehner, Susanne (International Geoscience and Remote Sensing Symposium (IGARSS), 2017)
Certain marine bacteria found in the near-surface layer of the ocean are expected to play an important role in the production and decay of surface active materials. Identifying a connection between marine bacteria and the production of natural surfactants may provide a better understanding of the global picture of biophysical processes at the boundary between the ocean and atmosphere, air-sea exchange of gases, and production of climate-active marine aerosols. Kurata et al. (2016) and Hamilton et al. (2015) have developed measurement methodology combining DNA sampling of sea surface microlayer with SAR satellite technology. Following Franklin et al. (2005) and Cunliffe et al. (2011), these authors used polycarbonate membrane filters in order to minimize potential contamination that may occur with other sampling techniques. A hydrophilic polycarbonate filter, attached to the sea surface by capillary forces, collected bacteria effectively from a 35-42 μm surface layer. A fly fishing technique was used in Kurata et al. (2016) and Hamilton et al. (2015) to ensure that the filter sat on the sea surface for a few seconds (away from the vessel and its wake in order to avoid these sources of disturbance to measurements of the microlayer). Samples from the water column at approximately 0.2 m depth were taken with a peristaltic pump for comparison with the sea surface results.
CRIS-Team Scopus Importer:2024-03-18